Regulation of Regenerative Periodontal Healing by NAMPT. (28th October 2013) - Nokhbehsaim, Marjan; Keser, Sema; Jäger, Andreas; Jepsen, Søren; Deschner, James
Abstract : Periodontitis is an inflammatory disease characterized by destruction of the tooth-supporting tissues. Obese individuals have an increased risk of periodontitis, and elevated circulating levels of nicotinamide phosphoribosyltransferase (NAMPT) may be a pathomechanistic link between both diseases. Recently, increased levels of NAMPT have also been found in patients with periodontitis, irrespective of the presence of obesity. This in vitro study sought to examine the effects of NAMPT on the regenerative capacity of human periodontal ligament (PDL) cells and, thereby, periodontal healing. PDL cells treated with enamel matrix derivative (EMD), which was used to mimic regenerative healing conditions in vitro, were grown in the presence and absence of NAMPT for up to 14 d. EMD stimulated significantly (P < 0.05 ) the expression of growth factors and their receptors, matrix molecules, osteogenesis-associated factors, and wound closure and calcium accumulation. In the presence of NAMPT, all these stimulatory effects were significantly (P < 0.05 ) reduced. In conclusion, the beneficial effects of EMD on a number of PDL cell functions critical for periodontal regeneration are counteracted by NAMPT. Enhanced levels of NAMPT, as found in obesity and periodontal inflammation, may compromise the regenerative capacity of PDL cells and, thereby, periodontal healing in the presence of EMD.